An African Night's Entertainment - Ekwensi, Cyprian (Pilgrim Books Ltd, 1962)
This is the story of vengeance.The girl who Abu is to marry marries another man, and Abu searches far and wide for someone who knows how to wreak vengeance.
Keywords: Juvenile Fiction